The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1253/circj.cj-10-0292
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Effects of Calcium Channel Blockers in Patients With Vasospastic Angina - A Meta-Analysis -

Abstract: Background: Although calcium channel blockers (CCB) are highly effective for suppression of vasospastic angina (VSA) attacks, their prognostic effects in VSA patients remain to be examined in a large number of patients. Methods and Results:Databases for related papers were searched and then a meta-analysis regarding the effects of CCB on major adverse cardiovascular events (MACE) in Japanese VSA patients with the 4 previous studies was performed. A total of 1,997 patients with positive coronary spasm provocati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 24 publications
0
59
0
2
Order By: Relevance
“…However, it is possible that the long-acting CCB benidipine-based treatment in the COPE trial would result in little difference in cardiac ischemic events between the β-blocker group and the other 2 groups, because benidipine is beneficial for preventing cardiac events caused by vasospastic angina. 13 Further studies are required to confirm the results of this study of the secondary prevention of patients with hypertension and coronary artery disease.…”
Section: Japanese Hypertensive Patientsmentioning
confidence: 82%
See 1 more Smart Citation
“…However, it is possible that the long-acting CCB benidipine-based treatment in the COPE trial would result in little difference in cardiac ischemic events between the β-blocker group and the other 2 groups, because benidipine is beneficial for preventing cardiac events caused by vasospastic angina. 13 Further studies are required to confirm the results of this study of the secondary prevention of patients with hypertension and coronary artery disease.…”
Section: Japanese Hypertensive Patientsmentioning
confidence: 82%
“…15 In addition, no apparent differences were observed in concomitant medication usage, such as antiplatelets, lipid-lowering drugs, ment effects than the others. 13 The Combination Therapy of Hypertension to Prevent Cardiovascular Events (COPE) trial is the first clinical trial to examine benidipine-combination therapy for the treatment of hypertension in Japan. 14, 15 The trial results demonstrated that both the percentages of subjects achieving the target blood pressure (BP) and the incidences of primary composite cardiovascular endpoints were similar among the benidipine-thiazide diuretic (thiazide), benidipineangiotensin-receptor blocker (ARB), and benidipine-β-blocker groups.…”
Section: Demographic and Baseline Patient Characteristics And Bp Contmentioning
confidence: 99%
“…These agents have been shown to reduce symptomatic angina episodes, 56-62 suppress inducible coronary spasm, 60 and most importantly are an independent determinant of preventing MACE in vasospastic angina patients. 33, 63 Nitrates have been used since the first description of vasospastic angina and are effective in reducing anginal episodes, 57 although their efficacy in reducing MACE is not evident. 64, 65 Nicorandil is a potassium-channel opener with nitrate-like effects that is extensively used in Japan for the treatment of vasospastic angina.…”
Section: Pharmacological Therapiesmentioning
confidence: 99%
“…[35][36][37][38] From now on, it seems important to select drugs by considering the class effects of CCB on the inhibition of cardiovascular accidents. Study limitations: First, it should be remembered that the current study adopted a switchover design and did not carefully investigate potential differences between different drugs (Ltype CCBs, T-type CCB).…”
Section: Discussionmentioning
confidence: 99%